Inter-Religious Dialogue: the Nigerian Experience, by Prof. Murtala A. Bidmos. Abuja, Panaf Publishing 2006.161pp. ISBN 978-37049-4-X. - Rufai’, Saheed Ahmad (Journal of Al-Tamaddun, 2012)
No abstract - book review